Orthostatic Hypotension: Definition, Pathophysiology, Classification, Prognostic Aspects, Diagnostics and Treatment - O. D. Ostroumova; M. S. Cherniaeva; M. M. Petrova; O. V. Golovina (Рациональная фармакотерапия в кардиологии, 2018)
The urgency of the problem of orthostatic hypotension (OH) has increased in recent years. It was due to the high prevalence and its adverse effect on the prognosis and  quality of life of patients, especially the elderly and  oldest old. The purpose of this review was to summarize the contemporary domestic and foreign literature data  about disease. The article presents an updated definition of OH, modern classification, pathophysiology, feature of the  course  of OH in the  elderly, recommendations for diagnosis and  treatment. Particular attention is paid to reviewing the  results of scientific research on the  influence of OH on the  risk of developing coronary  and  cerebrovascular events  and  overall mortality. OH is one  of the  forms  of orthostatic tolerance and diagnostic criteria were determined by the 2011 Consensus as a sustained fall of systolic blood pressure by at least 20 mm Hg and/or a diastolic blood pressure by 10 mm Hg within 3 min of standing. The prevalence of OH ranges depending on the age of the patients and the presence of a number of concomitant diseases: from 6% in healthy people without arterial hypertension up to 50% or more in people older than 75 years with a comorbid pathology. OH is an independent predictor of overall mortality and adverse  cardiovascular events.  OH is associated with an increased risk of serious adverse  cerebrovascular and  coronary  events,  and  may also contribute to cognitive impairment and  the  development of dementia. For today, we have three  clinical options OH: classical, early and delayed OH. In addition, OH is classified based  on etiology – primary and secondary; and pathophysiological principle – neurogenic OH and not a neurogenic OH (or functional). The algorithm for identifying patients with a high risk of development of OH and diagnostic methods are also presented. Non-medicamentous and medicamentous methods of OH treatment are considered.